2018
DOI: 10.1159/000493420
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Profiles of Kawasaki Disease Noted over Time in Suzhou, China

Abstract: Objectives: The purpose of the present study was to explore the changes in epidemiological, clinical and laboratory characteristics of Kawasaki disease (KD) over a 12-year period in this area. Methods: The medical records of KD patients hospitalized in the Children’s Hospital of Soochow University from January 2006 to December 2017 were retrospectively reviewed and analyzed. To elucidate the changes more clearly in these years, we divided all patients into three groups according to the time of admission, 5-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…A 12-year clinical study also confirmed that neutrophils were significantly increased in the acute phase of KD (42). Following IVIG treatment, neutrophils were frequently significantly decreased (42). Data on changes in neutrophils were consistent with these reports (41,42).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A 12-year clinical study also confirmed that neutrophils were significantly increased in the acute phase of KD (42). Following IVIG treatment, neutrophils were frequently significantly decreased (42). Data on changes in neutrophils were consistent with these reports (41,42).…”
Section: Discussionsupporting
confidence: 76%
“…Andreozzi et al (41) indicated that neutrophils were significantly increased in patients with acute-phase KD, since neutrophils in the reserve pool of the bone marrow were released into the peripheral circulation. A 12-year clinical study also confirmed that neutrophils were significantly increased in the acute phase of KD (42). Following IVIG treatment, neutrophils were frequently significantly decreased (42).…”
Section: Discussionmentioning
confidence: 69%
“…2. Sun et al similarly described a recent increase in incidence of KD among patients 1-5 years old in China in 2017 [23]. The annual incidence rates found in this study for all ages and < 5 years were 9.84 and 21.37 per 100,000 person-years, respectively.…”
Section: Incidence Of Kawasaki Diseasesupporting
confidence: 64%
“…However, our study partly revealed the demographic characteristics in this area. We had previously described an increasing number of KD patients in this area (17), with no focus on infantile KD. Here when we divided all 194 infantile KD into small groups according to calendar years, we found that although there was a stable increase of all infantile KD, the proportion of iKD seemed to be decreasing, which was inconsistent with the overall trend of KD as we reported (17).…”
Section: Discussionmentioning
confidence: 99%
“…We had previously described an increasing number of KD patients in this area (17), with no focus on infantile KD. Here when we divided all 194 infantile KD into small groups according to calendar years, we found that although there was a stable increase of all infantile KD, the proportion of iKD seemed to be decreasing, which was inconsistent with the overall trend of KD as we reported (17). As the etiology and mechanisms of the disease were not fully understood, the divergences might be related to the pathogenesis in infants whose immune system was not well-developed.…”
Section: Discussionmentioning
confidence: 99%